Development and genetics of red coloration in the zebrafish relative Danio albolineatus - Huang, Delai; Lewis, Victor M; Foster, Tarah N; Toomey, Matthew B; Corbo, Joseph C; Parichy, David M (eLife, 2021)
Animal pigment patterns play important roles in behavior and, in many species, red coloration serves as an honest signal of individual quality in mate choice. Among Danio fishes, some species develop erythrophores, pigment cells that contain red ketocarotenoids, whereas other species, like zebrafish (D. rerio) only have yellow xanthophores. Here, we use pearl danio (D. albolineatus) to assess the developmental origin of erythrophores and their mechanisms of differentiation. We show that erythrophores in the fin of D. albolineatus share a common progenitor with xanthophores and maintain plasticity in cell fate even after differentiation. We further identify the predominant ketocarotenoids that confer red coloration to erythrophores and use reverse genetics to pinpoint genes required for the differentiation and maintenance of these cells. Our analyses are a first step toward defining the mechanisms underlying the development of erythrophore-mediated red coloration in Danio and reveal striking parallels with the mechanism of red coloration in birds.
Keywords: pigmentation; Danio; color pattern; erythrophore; carotenoid